2014
DOI: 10.1177/0165551514535710
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Spanish lexical resources by meta-classifiers for polarity classification

Abstract: In this paper we focus on unsupervised sentiment analysis in Spanish. The lack of resources for languages other than English, as for example Spanish, adds more complexity to the task. However, we take advantage of some good already existing lexical resources. We have carried out several experiments using different unsupervised approaches in order to compare the different methodologies for solving the problem of the Spanish polarity classification in a corpus of movie reviews. Among all these approaches, perhap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…The iSOL is composed of 2509 positive and 5626 negative words, thus the Spanish lexicon has 8135 opinion words in total. This resource has been successfully evaluated in several corpora and the results showed that the use of an improved list of sentiment words could be considered a good strategy for unsupervised polarity classification [32][33][34].…”
Section: Sentiment Analysis On Twittermentioning
confidence: 99%
“…The iSOL is composed of 2509 positive and 5626 negative words, thus the Spanish lexicon has 8135 opinion words in total. This resource has been successfully evaluated in several corpora and the results showed that the use of an improved list of sentiment words could be considered a good strategy for unsupervised polarity classification [32][33][34].…”
Section: Sentiment Analysis On Twittermentioning
confidence: 99%
“…Another approach for building a monolingual SA system for a new language is based on the use of machine translation (MT) in order to translate the text into English automatically, to then apply a polarity classifier for English, yielding as a result a kind of cross-language sentiment analysis system (Balahur and Turchi, 2012b;Wan, 2009;Perea-Ortega et al, 2013;Martínez Cámara et al, 2014). It was found that text with more sentiment is harder to translate than text with less sentiment (Chen and Zhu, 2014) and that translation errors produce an increase in the sparseness of features, a fact that degrades performance (Balahur and Turchi, 2012a;.…”
Section: Multilingual Samentioning
confidence: 99%
“…As in the previous study the results demonstrate that the combination of sentiment classification models enhances the final performance of the system. The lack of linguistic resources for sentiment analysis in Spanish was the excuse for Martínez-Cámara et al [48] to utilize a stacking architecture to classify Spanish movie reviews. The authors employ a parallel corpus in English and Spanish to enhance the results of a classifier of Spanish reviews.…”
Section: State Of the Art Of Absamentioning
confidence: 99%